1980
DOI: 10.1002/1097-0142(19800615)45:12<2940::aid-cncr2820451208>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Host-tumor interaction and nutrient supply

Abstract: Adequate parenteral nutritional support improves nutritional status in cancer patients, but its effect on tumor growth remains controversial. Using a transplantable mammary adenocarcinoma in a rat-TPN model, the relative effect of different exogenous intravenous nutrients on tumor growth and host maintenance was studied. Relative to chow controls, starvation increased host depletion without reducing tumor growth. Adequate carbohydrate calories alone neither improved host maintenance nor stimulated tumor growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…These findings give support for parenteral nutrition studies in the wasted cancer patient where some consideration is now being given to the parenteral infusion of lipid, rather than glucose, with potential benefits in the maintenance of body weight and lack of tumour progression (Magee et al, 1979;Conyers et al, 1979b;Buzby et al, 1980;Brennan, 1981).…”
Section: Blood and Liver Metabolitesmentioning
confidence: 70%
See 1 more Smart Citation
“…These findings give support for parenteral nutrition studies in the wasted cancer patient where some consideration is now being given to the parenteral infusion of lipid, rather than glucose, with potential benefits in the maintenance of body weight and lack of tumour progression (Magee et al, 1979;Conyers et al, 1979b;Buzby et al, 1980;Brennan, 1981).…”
Section: Blood and Liver Metabolitesmentioning
confidence: 70%
“…While the effect of starvation on tumour growth in experimental animals has been considered (Goodgame et al, 1979;Buzby et al, 1980), little information is available on the extent to which tumour-bearing modifies the normal ketonaemic response to starvation. In the study reported here, we describe the metabolic adaptation to starvation in tumour-bearing and control mice after periods of identical dietary intake.…”
mentioning
confidence: 99%
“…We hypothesized that reduction of protein thiol values in serum of females with MGT in the second group in our study might have been due to the higher rate of protein oxidation or increased uptake of antioxidants by tumourous tissues. Buzby et al (1980) described that malignant cells could scavenge antioxidants from circulation for their supplement. The value of non-protein thiols in serum was higher in females of group 2 under anaesthesia 10 min after surgery than in healthy anaesthetized females of (control) group 3.…”
Section: Discussionmentioning
confidence: 99%
“…GST is vital antioxidant present in cells. Rapid GST synthesis in tumour cells is associated with high rates of cell proliferation, while GSH depletion is sufficient to sensitize cancer cells to the cytotoxic effects of oxidative and nitrative stress and make them more defenseless to the effects of anticancer drugs or the genes that promote apoptosis [22].…”
Section: Resultsmentioning
confidence: 99%